2014
DOI: 10.1136/bmjopen-2014-005133
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking at home is a risk factor for community-acquired pneumonia in older adults: a population-based case–control study

Abstract: ObjectiveTo assess whether passive smoking exposure at home is a risk factor for community-acquired pneumonia (CAP) in adults.SettingA population-based case-control study was designed in a Mediterranean area with 860 000 inhabitants >14 years of age.Participants1003 participants who had never smoked were recruited.Primary and secondary outcome measuresRisk factors for CAP, including home exposure to passive smoking, were registered. All new cases of CAP in a well-defined population were consecutively recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
(23 reference statements)
1
15
1
Order By: Relevance
“…5,32 These findings are consistent with those of other studies that demonstrate that the risk of death from pneumonia is reduced to the level of nonsmokers 10 years after giving up smoking The impact of passive smoking is still not well understood; although most studies have observed no significant effect in the overall population, an effect has been described for people aged 65 years and older. 34 It would seem that the effect of passive smoking is enhanced by age; thus, whereas the defense mechanisms of younger people would be sufficient to counter the effects of others' smoking, the more diminished lung defense mechanisms of the elderly would be overwhelmed.…”
Section: Smoking Habitmentioning
confidence: 97%
“…5,32 These findings are consistent with those of other studies that demonstrate that the risk of death from pneumonia is reduced to the level of nonsmokers 10 years after giving up smoking The impact of passive smoking is still not well understood; although most studies have observed no significant effect in the overall population, an effect has been described for people aged 65 years and older. 34 It would seem that the effect of passive smoking is enhanced by age; thus, whereas the defense mechanisms of younger people would be sufficient to counter the effects of others' smoking, the more diminished lung defense mechanisms of the elderly would be overwhelmed.…”
Section: Smoking Habitmentioning
confidence: 97%
“…32 In addition to the direct effects of smoking (eg, COPD, heart disease) on the incidence of pneumonia in the elderly, exposure to secondhand smoke was recently shown to increase the risk of pneumonia in the elderly by over 1.5 times. 33 Interestingly, this effect was seen only in those over the age of 65 years and was not observed in the younger cohort.…”
Section: Comorbid Conditionsmentioning
confidence: 88%
“…[45,46] A study published by Bello et al [47] showed that current smokers with pneumococcal CAP often develop severe sepsis and require hospitalization at a younger age despite fewer comorbid conditions. Almirall et al, [48] in a recent study, found that passive smoking at home is a risk factor for CAP in older adults (≥65 years).…”
Section: Lifestyle Factorsmentioning
confidence: 96%